Efficacy of Adjuvant Tamsulosin for Improving the Stone Free Rate after Extracorporeal Shock Wave Lithotripsy in Renal Stones - Iqbal Shahzad, Khadim Hussain, Muhammad Ali Yousuf, Mumtaz Manzoor, Ghulam Mustafa Pathan, Tanveer Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary aim of this investigation was to appraise the effectiveness of supplementary tamsulosin in augmenting the stone-free rate subsequent to extracorporeal shock wave lithotripsy (ESWL) in managing renal calculi. Study Design: Employing a randomized controlled trial methodology, participants diagnosed with renal calculi were allocated to either a control group or an experimental group receiving tamsulosin. The experimental group was administered oral tamsulosin concomitantly with ESWL, whereas the control group underwent ESWL exclusively. Method: This study was conducted at Liaquat National Hospital Karachi in the duration from June, 2022 to November, 2022 over 100 patients presenting with renal calculi was enrolled and indiscriminately segregated into two equivalent groups, each containing 50 participants. Those in the tamsulosin group were prescribed oral tamsulosin for a four-week period before and after ESWL, while the control group received ESWL alone. The primary outcome metric was the stone-free rate following a three-month treatment regimen. Results: The tamsulosin group demonstrated a significantly elevated stone-free rate in comparison to the control group (80% vs 60%, p<0.05). No significant disparities were observed between the groups with regard to adverse events. Discussion: The findings of this investigation propose that supplementary tamsulosin may enhance the stone-free rate subsequent to ESWL in the management of renal calculi. This discovery carries implications for renal calculi treatment, potentially leading to improved outcomes and diminished recurrence rates. Keywords: Tamsulosin, Renal calculi, ESWL, Stone-free rate, Randomized controlled trial.